PENINGKATAN KETERAMPILAN ENTREPRENEURSHIP PESERTA DIDIK SEKALIGUS MENYOKONG TERWUJUDNYA LINGKUNGAN SEKOLAH ADIWIYATA MELALUI PROGRAM KREATIVITAS DAUR ULANG SAMPAH - Moh. Kamal Halim; Ainun Jariah; Annida Elfiana Citra Ardianty; Burhanuddin Ronggopuro; Nita Dwi Indahsari; Habiddin Habiddin; Moh. Kamal Halim; Ainun Jariah; Annida Elfiana Citra Ardianty; Burhanuddin Ronggopuro; Nita Dwi Indahsari (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Waste poses a significant environmental threat, leading to the spread of diseases, water pollution, flooding, unpleasant odors, and general discomfort. Despite its negative impacts, waste holds immense economic potential. Recycling can transform waste into valuable resources, boosting the economy. This study analyzes the waste recycling creativity program at SMPN 7 Malang, examining its effectiveness in enhancing students' entrepreneurship skills and supporting the realization of the Adiwiyata School Environment. Employing a qualitative descriptive approach, data was collected through interviews, observations, and documentation. The findings reveal the successful implementation of the waste recycling creativity program at SMPN 7 Malang, demonstrating its positive impact on students' entrepreneurship skills. Students are trained to transform waste into marketable products, such as bags, pencil cases, wall decorations, and more. Additionally, the program contributes to the realization of the Adiwiyata School Environment by reducing waste in the school premises and students' neighborhoods.